Pengaruh tata letak gudang terhadap kelancaran distribusi barang ke konsumen di kantor cabang alfamart Kotabumi. - Anisa Utami; Vicky F. Sanjaya (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
Â PT. Sumber Alfaria Trijaya, Tbk (AMRT) is engaged in the retail distribution of consumer goods through the operation of the "Alfamart" minimarket network. The mini market network consists of mini markets, has direct ownership and is based on a franchise agreement. Special goods, namely domestic goods, several types of goods distributed by PT during the processing. Sumber Alfaria Trijaya, Tbk, namely cosmetics, food, non-food, daily necessities, etc. One way of distributing goods to consumers is warehouse management. This study uses a qualitative method. The population in this study were warehouse employees of PT. Sumber Alfaria Trijaya, Tbk Kotabumi branch. The data collection technique used was a questionnaire, which gave 10 questions to each respondent, then processed the data through SPSS statistical analysis. The result is that the layout of the warehouse has a positive and significant effect on the stability of the distribution of goods to consumers..Â Â